2022
DOI: 10.1186/s13287-021-02690-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of mesenchymal stem cells in peripheral nerve injury

Abstract: Various immune cells and cytokines are present in the aftermath of peripheral nerve injuries (PNI), and coordination of the local inflammatory response is of great significance for the recovery of PNI. Mesenchymal stem cells (MSCs) exhibit immunosuppressive and anti-inflammatory abilities which can accelerate tissue regeneration and attenuate inflammation, but the role of MSCs in the regulation of the local inflammatory microenvironment after PNI has not been widely studied. Here, we summarize the known intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 133 publications
0
41
0
Order By: Relevance
“…They found a significantly higher infiltration of M2 macrophages in response to the SIS Axoguard conduits but a predominant infiltration of M1 macrophages in response to the NeuraGen Nerve Guide conduits [ 70 ]. In addition to immunomodulatory biomaterials, it is well known that MSCs of different tissue origins can potently promote pro-regenerative (M2) macrophage polarization while inhibiting pro-inflammatory (M1) macrophage activation both in vitro and in various preclinical disease models [ 14 ]. MSCs exert their therapeutic effects on PNI possibly through their dual functions, multipotent differentiation capacity into neural type of cells and their paracrine secretion of an array of bioactive factors with multiple trophic effects on both neural and nonneural cells [ 13 ], whereby the potent immunomodulatory effects of MSCs on immune cells, particularly macrophages, may constitute one of the major mechanisms by which MSCs exert their therapeutic effects on PNI [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found a significantly higher infiltration of M2 macrophages in response to the SIS Axoguard conduits but a predominant infiltration of M1 macrophages in response to the NeuraGen Nerve Guide conduits [ 70 ]. In addition to immunomodulatory biomaterials, it is well known that MSCs of different tissue origins can potently promote pro-regenerative (M2) macrophage polarization while inhibiting pro-inflammatory (M1) macrophage activation both in vitro and in various preclinical disease models [ 14 ]. MSCs exert their therapeutic effects on PNI possibly through their dual functions, multipotent differentiation capacity into neural type of cells and their paracrine secretion of an array of bioactive factors with multiple trophic effects on both neural and nonneural cells [ 13 ], whereby the potent immunomodulatory effects of MSCs on immune cells, particularly macrophages, may constitute one of the major mechanisms by which MSCs exert their therapeutic effects on PNI [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to immunomodulatory biomaterials, it is well known that MSCs of different tissue origins can potently promote pro-regenerative (M2) macrophage polarization while inhibiting pro-inflammatory (M1) macrophage activation both in vitro and in various preclinical disease models [ 14 ]. MSCs exert their therapeutic effects on PNI possibly through their dual functions, multipotent differentiation capacity into neural type of cells and their paracrine secretion of an array of bioactive factors with multiple trophic effects on both neural and nonneural cells [ 13 ], whereby the potent immunomodulatory effects of MSCs on immune cells, particularly macrophages, may constitute one of the major mechanisms by which MSCs exert their therapeutic effects on PNI [ 14 ]. Our previous studies showed that GMSCs possess potent immunomodulatory effects on pro-inflammatory (M1)/pro-regenerative (M2) macrophages both in vitro and in mice skin wound models [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs can be considered as interesting candidates to develop new therapeutic approaches to counteract ND thanks to these properties, together with the immunomodulatory capacity and the possibility to be isolated by autologous and allogeneic sources [26,31,32].…”
Section: Mscs Preconditioning In Neurological Diseasesmentioning
confidence: 99%
“…Mesenchymal stem cells are pluripotent stem cells with multiple biological potentials, such as regeneration, immunomodulation, repair of damaged tissues, home to the site of injury, and other properties ( 11 13 ). Currently, mesenchymal stem cell (MSC) treatment positively affects diseases.…”
Section: Introductionmentioning
confidence: 99%